Pemodelan Spasial Penentuan Instrumen Srategis Penataan Ruang Untuk Pengendalian Risiko Banjir di Wilayah Jabodetabek - H.R. Sunsun Saefulhakim (Jurnal Ilmu Pertanian Indonesia, 2011)
Spatial planning must perform protection on socioeconomic and ecological functions of space, and prevent negative impacts of space utilization on the environment. Constraints on such spatial planning increase continuously. In the Jadebotabek Region 2003 to 2006, flood-risky households increased with annual rate more than four times economic growth. This research aimed to determine strategic spatial planning instruments to control flood risks, by using Spatial Durbin Modeling approach. The model specifies explanatory variables into local and external. Local variables give effects as in a conventional regression model, while external variables give effects in a given pattern represented by a spatial contiguity matrix. Principal Components Analysis was employed to reduce multicollinearities among variables. Test and parameter estimation of the model were employed by using Forward Stepwise General Regression Model with ANOVA-Iike design and Sigma-Restricted Parametrization. Research area was Jadebotabek Region year 2003 excluding Kepulauan Seribu, constituted 12 districts and sevent watersheds. Measurement units were administrative regions at village level (1.488 units). The model fit to the data very significantly (R2=0.84; p<.